2021
DOI: 10.5194/os-17-265-2021
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of the Atlantic Meridional Overturning Circulation at 11° S inferred from bottom pressure measurements

Abstract: Abstract. Bottom pressure observations on both sides of the Atlantic basin, combined with satellite measurements of sea level anomalies and wind stress data, are utilized to estimate variations of the Atlantic Meridional Overturning Circulation (AMOC) at 11∘ S. Over the period 2013–2018, the AMOC and its components are dominated by seasonal variability, with peak-to-peak amplitudes of 12 Sv for the upper-ocean geostrophic transport, 7 Sv for the Ekman and 14 Sv for the AMOC transport. The characteristics of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Note, when we update the MOC estimate from the pilot configuration (Meinen, Speich, Perez, et al., 2013; Meinen, Speich, Piola, et al., 2018), we also use CCMP zonal wind stress from 2009 to 2010. Nevertheless, it has been shown that at 34.5°S different wind products generate similar values for the Ekman transport (Garzoli & Baringer, 2007), while at other latitudes (e.g., 11°S, Herrford et al., 2021) the choice of the wind product might be critical.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note, when we update the MOC estimate from the pilot configuration (Meinen, Speich, Perez, et al., 2013; Meinen, Speich, Piola, et al., 2018), we also use CCMP zonal wind stress from 2009 to 2010. Nevertheless, it has been shown that at 34.5°S different wind products generate similar values for the Ekman transport (Garzoli & Baringer, 2007), while at other latitudes (e.g., 11°S, Herrford et al., 2021) the choice of the wind product might be critical.…”
Section: Methodsmentioning
confidence: 99%
“…To address this observational gap, moored arrays have been deployed at several latitudes as part of an international initiative to study the South Atlantic MOC (SAMOC; Ansorge et al., 2014; Garzoli & Matano, 2011; Herrford et al., 2021; Hummels et al., 2015; Kersalé, Meinen, et al., 2020; Kopte et al., 2017; Meinen, Speich, Perez, et al., 2013; Meinen, Speich, Piola, et al., 2018). One of the major components of this initiative is the South Atlantic MOC Basin‐wide Array (SAMBA; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The first component, T GS , has been measured by submarine telephone cables in the Florida Straits since 1982 (Baringer and Larsen, 2001;Meinen et al, 2010) (https:// www.aoml.noaa.gov/phod/floridacurrent/index.php, last access: 7 September 2020). The second component, T EK , is derived from zonal wind stress from ERA5 reanalysis products (Hersbach et al, 2020). The third component, T UMO , is the sum of the western boundary wedge transport (T WBW ), the hypsometric mass compensation (T EXT ), and the internal geostrophic transport (T INT ) over the top 1100 m. T WBW is the northward transport measured between the Abaco Island continental shelf and the WB2 mooring.…”
Section: Rapid Transport Estimates and Slamentioning
confidence: 99%
“…Other international efforts to measure the AMOC via mooring array programmes include SAMBA (South Atlantic MOC Basin-wide Array) at 34.5 • S (Meinen et al, 2018;Kersale et al, 2020), TRACOS (Tropical Atlantic Circulation and Overturning) at 11 • S (Hummels et al, 2015;Herrford et al, 2021), and OSNAP (Overturning in the Subpolar North Atlantic Program) in the subpolar North Atlantic (Lozier et al, 2019). RAPID and these other mooring array programmes have made step-change advancements in our understanding of the AMOC over the last 15 years (Frajka-Williams et al, 2019); however, they are limited to a single line of latitude and alone cannot be used to infer upstream-downstream changes in the larger-scale structure of the AMOC.…”
mentioning
confidence: 99%
“…In recent years, observations of the BC have increased as the AMOC observing network has expanded into the South Atlantic (e.g., Ansorge et al, 2014;Frajka-Williams et al, 2019;Garzoli et al, 2012;Hummels et al, 2015;Meinen et al, 2013Meinen et al, , 2018Kersalé et al, 2020;Herrford et al, 2021). One element of this AMOC observing network, the South Atlantic MOC Basin-wide Array (SAMBA) has been under development at 34.5°S since 2009, and is presently being used to observe daily variations in the AMOC (Meinen et al, 2013(Meinen et al, , 2018Kersalé et al, 2020).…”
mentioning
confidence: 99%